THE RELATIONSHIP BETWEEN FREQUENCY OF LISTENING AND VOCABULARY MASTERY TOWARD LISTENING ABILITY AT THE FIRST GRADE STUDENTS OF MAN 4 KEDIRI - Tias, Aprilia Ayuning; Putri, Kristanti Yuntoro (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
In this research, the researcher examined the correlation between frequency of listening and vocabulary mastery toward listening ability at first grade students of MAN 4 Kediri. The aim of the research was to find out (1) the students’ frequency of listening, (2) the students’ vocabulary mastery, (3) the students’ listening, (4) the significant simultaneous relationship between frequency of listening and vocabulary mastery toward listening ability, and (5) the significant partial relationship between frequency of listening and vocabulary mastery toward listening ability at the first grade students at MAN 4 Kediri. This research can be categorized as Quantitative correlation. The technique to collect data was the questionnaire and test. The questionnaire used to collect the data of frequency of listening and the test was for collecting the data of vocabulary mastery and listening ability. The instrument contained of 20 questions for each variable. In this case, the first grade students of science classes, totally 136 students, were taken as population and 100 students as sample by Sloven formula. The result of students’ frequency of listening is that 75% or 75 students are in good category. For the students’ vocabulary mastery, there are 43% or 43 students who are in very good category. The students’ listening ability is 30% or that 30 students are in good category. To find out the correlation between three variables in this research used the SPSS 15,0 version. The result of significant level is 0,731 (a). It is more than 5% significant level. It means that there is no significant correlation between frequency of listening and vocabulary mastery toward listening ability at the first grade students of MAN 4 Kediri. So, the alternative hypothesis was rejected.